2023
DOI: 10.1126/sciimmunol.adg1487
|View full text |Cite
|
Sign up to set email alerts
|

Lung tumor–infiltrating T reg have divergent transcriptional profiles and function linked to checkpoint blockade response

Arbor G. Dykema,
Jiajia Zhang,
Laurene S. Cheung
et al.

Abstract: Regulatory T cells (T reg ) are conventionally viewed as suppressors of endogenous and therapy-induced antitumor immunity; however, their role in modulating responses to immune checkpoint blockade (ICB) is unclear. In this study, we integrated single-cell RNA-seq/T cell receptor sequencing (TCRseq) of >73,000 tumor-infiltrating T reg (TIL-T reg ) from anti–PD-1–treated and treatment-naive non–small cell lung cancers (NSCLC) with single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…7f). The Tregs in p1_C27 were highly expressed all tested markers except GITR, an immune checkpoint that was recently described to mark the most immune suppressive Treg subset in NSCLC and associated with PD-1 resistance ( 21 ). Some of the other communities expressed similar or higher levels of GITR on the Tregs ( p1_C26 , p1_C23 , p1_C6 , p1_C17 ) and showed above average expression of immune checkpoints on the CD4 + and CD8 + T cells ( p1_C7 , p1_C23 , p1_C17 , p1_C26) , more similar to the mouse T/DC community.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…7f). The Tregs in p1_C27 were highly expressed all tested markers except GITR, an immune checkpoint that was recently described to mark the most immune suppressive Treg subset in NSCLC and associated with PD-1 resistance ( 21 ). Some of the other communities expressed similar or higher levels of GITR on the Tregs ( p1_C26 , p1_C23 , p1_C6 , p1_C17 ) and showed above average expression of immune checkpoints on the CD4 + and CD8 + T cells ( p1_C7 , p1_C23 , p1_C17 , p1_C26) , more similar to the mouse T/DC community.…”
Section: Resultsmentioning
confidence: 97%
“…Yet, Chen et al similarly identified immune hubs associated with response to PD-1 blockade that were rich in stem-like (progenitor exhausted) TCF7 + PD-1 + CD8 + T cell and mregDCs, also containing Tregs ( 57 ). This indicates that a careful definition of the Treg communities, including cell states ( 21 ) and local cytokine environments, will be required in order to identify accurately predictive biomarkers for resistance to PD-1/PDL1 blockade. Spatial analysis of pre-treatment biopsies from cohorts such as ARCTIC( 58 ), MYSTIC( 59 ), and CHECKMATE 227,( 60 ) comparing anti-PDL1/PD-1 as monotherapy or in combination with anti-CTLA-4, could help to better define the Treg communities that confer resistance to blocking the PD-1/PD-L1 axis alone, yet may be responsive to the addition of Treg targeting.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in 4-1BB + Tregs was similarly associated with MPR to neoadjuvant CTLA-4 and PD-1 in HPV-negative HNC profiled by scRNA-seq 52 . The eTreg population, highly expressive of both GITR and OX40 , may be the Tregs subset that restricts response to PD-1 in lung cancer 53 . Our data are consistent with murine models that showed that higher CTLA-4 expression on Tregs explained their preferential depletion by CTLA4 ICB 54 , and that tumor response was dependent upon Fc competence to mediate ADCC and Treg depletion 34,35,54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Tregs were discovered in an ICIs responsive mouse tumor model to acquire a Th1-like transcriptional signature upon tumor entry, i.e., upregulation of T-bet and certain pro-inflammatory disease-related genes. Homology analysis revealed the existence of a similar subpopulation in human lung cancer, which is also enriched in tumors that respond to ICIs [ 162 ]. The study found that disruption of the CARD9-BCL10-MALT1 (CBM) signaling complex in TI-Tregs from mice resulted in loss of their inhibitory function and a shift to a pro-inflammatory, IFN-γ-secreting phenotype, leading to enhanced efficacy of anti-PD-1/PD-L1 antibodies [ 163 ].…”
Section: New Advances and Therapies For Targeting Tregs Against Tumorsmentioning
confidence: 99%